Pemberdayaan Lingkungan Berbasis Ecopesantren di Pondok Pesantren Darul Huffaz Lampung - Sari, Nurhalina; Natalina, Natalina; Saputra, Firman Dwi; Ardika, Muhammad Fajar; Rahmadhan, Arif (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The Darul Huffaz Islamic Boarding School has a problem with piles of rubbish, where up to now the rubbish has only been collected, transported, and thrown to the Pesawaran TPA. Eco-Islamic boarding school-based education is an activity to make Islamic boarding schools environmentally friendly through real action. The aim of this community service (PKM) is to carry out eco-Islamic boarding school-based environmental empowerment at the Darul Huffaz Islamic Boarding School. The PKM partner is the Darul Huufaz Islamic Boarding School with a target of 32 female student volunteers, teachers, and employees. The activities were carried out for five months, from July to November 2023. Environmental empowerment activities carried out were the creation of waste banks in Islamic boarding schools, the use of organic waste into compost, and inorganic waste into eco-bricks. This community service activity is carried out in stages, namely the situational analysis of partner conditions, socialization, implementation, monitoring, evaluation, and expansion. Mentoring and training activities resulted in an increase in the knowledge of residents at the Darul Huffaz Islamic Boarding School by 10%, the formation of waste bank peer educators, and a waste management program under the guidance of the Darul Huffaz Islamic Boarding School OSIS through compost and eco-bricks making activities. It is hoped that this PKM activity can become a learning method for developing eco-Islamic boarding school-based education at the Darul Huffaz Islamic Boarding Schools.